2006
DOI: 10.1016/j.amjhyper.2005.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Expression of Endothelial Connexins 43 and 37 in Hypertensive Rats Is Rectified After 7-Day Carvedilol Treatment

Abstract: The study showed that L-NAME-induced hypertension has differential effects on endothelial connexins, which respond variously to carvedilol and atenolol. In HUVEC carvedilol directly upregulates endothelial Cx43 and the effect is independent of its antioxidant activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 29 publications
1
42
0
Order By: Relevance
“…Previous studies have shown that direct intercellular communication through cell membrane protein channels made of connexins, called gap junctions, is involved in several steps of atherogenesis (Severs et al 2001;Haefliger et al 2004;Chadjichristos et al 2006). In animal studies, endothelial gap junctions have been reported to be downregulated in the presence of risk factors of atherosclerotic disease, such as aging (Yeh et al 2000a), hypertension (Yeh et al 2006), and hyperlipidemia (Yeh et al 2003b), in which endothelial dysfunction exists (Esper et al 2006). In addition, the downregulation of endothelial gap junctions in hypertension and hyperlipidemia can be, respectively, attenuated by antihypertensive and lipid-lowering drugs (Yeh et al 2003b(Yeh et al ,2006, which are known to improve impaired endothelial function (Esper et al 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that direct intercellular communication through cell membrane protein channels made of connexins, called gap junctions, is involved in several steps of atherogenesis (Severs et al 2001;Haefliger et al 2004;Chadjichristos et al 2006). In animal studies, endothelial gap junctions have been reported to be downregulated in the presence of risk factors of atherosclerotic disease, such as aging (Yeh et al 2000a), hypertension (Yeh et al 2006), and hyperlipidemia (Yeh et al 2003b), in which endothelial dysfunction exists (Esper et al 2006). In addition, the downregulation of endothelial gap junctions in hypertension and hyperlipidemia can be, respectively, attenuated by antihypertensive and lipid-lowering drugs (Yeh et al 2003b(Yeh et al ,2006, which are known to improve impaired endothelial function (Esper et al 2006).…”
mentioning
confidence: 99%
“…In animal studies, endothelial gap junctions have been reported to be downregulated in the presence of risk factors of atherosclerotic disease, such as aging (Yeh et al 2000a), hypertension (Yeh et al 2006), and hyperlipidemia (Yeh et al 2003b), in which endothelial dysfunction exists (Esper et al 2006). In addition, the downregulation of endothelial gap junctions in hypertension and hyperlipidemia can be, respectively, attenuated by antihypertensive and lipid-lowering drugs (Yeh et al 2003b(Yeh et al ,2006, which are known to improve impaired endothelial function (Esper et al 2006). The evidence has suggested that downregulation of gap junctions in the endothelium reflects endothelial dysfunction.…”
mentioning
confidence: 99%
“…In the mesenteric artery of the same rat model, Kansui et al (2004) showed that the Cx37 and Cx40 were downregulated and the Cx43, though scarce and heterogenous, was upregulated. In the tail artery of rat with N-nitro-L-arginine methyl ester-induced hypertension, Yeh et al (2006) demonstrated that the endothelial Cx37 and Cx43 were downregulated and the Cx40 remained unchanged. When compared with the resistant arteries, the baseline pressure of the venous vessels before being anastomosed with the arteries is much lower.…”
Section: Discussionmentioning
confidence: 99%
“…Some special membrane domains composed of aqueous intracellular channels provide direct cytoplasmic connections between cells, and allow for the passage of ions or small molecules between adjacent cells, thus ECs and OBs can communicate and exchange information (Dbouk et al 2009). Several predominant gap junction proteins including Cx43, Cx37 and Cx40 have been identified to express in ECs and OBs (Yeh et al 2006). Similarly, the communication via Cx43 gap junctions can promote the expression of osteoblastic differentiation markers such as alkaline phosphatase (ALP), osteocalcin (OC) and bone sialoprotein in OBs (Guillotin et al 2008).…”
Section: Interaction Between Osteoblasts and Endothelial Cellsmentioning
confidence: 99%